2005
DOI: 10.1016/j.mod.2005.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specificity of hedgehog repression by the Polycomb group during Drosophila melanogaster development

Abstract: During embryogenesis and wing disc morphogenesis in Drosophila, different developmental mechanisms are used along the antero-posterior (A-P) axis. The establishment of antero-posterior polarity requires the secreted protein Hedgehog, which is only expressed in P compartments and which is a key effector of the Engrailed transcription factor. At the same time, it is essential that both engrailed and hedgehog (hh) remain in a repressed state in A compartments. In this article, we show that hh is maintained in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…For example, terminally differentiated cells of the salivary glands from third instar larvae do not express CycA (Edgar and Orr-Weaver 2001), but neither the endogenous gene nor the isolated PRE are able to attract PcG proteins in this tissue. This situation is similar to the hh gene, which is a known target of PcG proteins (Chanas and Maschat 2005). Another chromatin-silencing activity must therefore be responsible for this silencing.…”
Section: Dynamic Repression Versus Stable Silencing Of the Cyca Gene mentioning
confidence: 75%
“…For example, terminally differentiated cells of the salivary glands from third instar larvae do not express CycA (Edgar and Orr-Weaver 2001), but neither the endogenous gene nor the isolated PRE are able to attract PcG proteins in this tissue. This situation is similar to the hh gene, which is a known target of PcG proteins (Chanas and Maschat 2005). Another chromatin-silencing activity must therefore be responsible for this silencing.…”
Section: Dynamic Repression Versus Stable Silencing Of the Cyca Gene mentioning
confidence: 75%
“…This underlines the importance of tissue specificity. Indeed, many studies have shown genetically that the PcG and TrxG genes have tissue-specific roles (Breen, 1999;Chanas and Maschat, 2005;Janody et al, 2004;Narbonne et al, 2004). It may well be that each type of adult stem cell in Drosophila uses a different set of PRE/TREs.…”
Section: Switching Upon Differentiation: Insights From Fliesmentioning
confidence: 99%
“…Moreover, a direct genetic interaction between en and the apoptotic machinery remains to be investigated. As en is known to have multiple interactions with other proteins (Alexandre and Vincent, 2003;Chanas and Maschat, 2005;Joly et al, 2007;Kobayashi et al, 2003), a complex regulatory network involving target proteins of en may be responsible for regulating apoptosis in a lineage-specific manner. Further analysis of interactions with such target proteins is necessary to reveal the full regulatory network in more detail.…”
Section: Research Articlementioning
confidence: 99%